The Impact of Harnessing Generative AI on Financial Modeling: An Analysis of Risks, Ethical Imperatives and Organizational Transformation - Abubakar, Adamu; Narvekar, Meera (Global journal of Business and Integral Security, 2026)
The non-technical implications of implementing Generative AI (GenAI) in the context of financial modeling were examined in this research by means of a qualitative multi-case study. The research explored related risks, ethical obligations, and changes organisations had in place by systematically reviewing public filings, reports, and disclosures. The results revealed an evolutionary riskemergence path from operational to strategic and system risks. It also disclosed that the values of accountability, transparency, and fairness are practically operationalised as significant risk reduction mechanisms rather than purely theoretical concepts. As a result, achieving such integration requires deep organizational change, such as workforce re-skilling and new governance frameworks. It is argued that GenAI engagement is first and foremost a strategic organizational challenge, rather than a technologically demanding one, which implies managing its nuanced consequences. This paper provides context for financial regulators, risk managers, and corporate strategists who are responsible for managing technological adoption.